Peak-intensity energy spectra of intense solar energetic electron events measured with Solar Orbiter in 2020-2022 - Fedeli, Annamaria; Dresing, Nina; Gieseler, Jan; Warmuth, Alexander; Schuller, Frederic; Gómez-Herrero, Raúl; Jebaraj, Immanuel Christopher; Espinosa, Francisco; Vainio, Rami (EDP Sciences, 2026)
Context
The energy spectra of energetic particles offer valuable insights into particle acceleration processes. While the commonly observed spectral breaks in solar energetic electron (SEE) spectra could serve as fingerprints of the acceleration process, several transport-related effects have been proposed to be responsible as well. Here, we analyse the energy spectra of intense SEE events measured with Solar Orbiter’s Energetic Particle Detector (EPD) between December 2020 and December 2022.
Aims
We investigate the shape of SEE spectra by fitting them with various mathematical models. We compare our results with previous studies and explore possible links to transport-related effects. We aim to identify potential correlations between spectral features and meaningful parameters, such as the radial distance, or the properties of associated solar events.
Methods
We determined the background-subtracted peak-intensity spectra as observed by EPD, accounting for velocity dispersion. We fit the spectra of STEP and EPT with various mathematical models, using an automated method that chooses the best possible fit.
Results
We found four different spectral shapes in our analysis: single power law, double power law and two types of triple power law: a knee-knee (KK) and an ankle-knee (AK) triple power law. No significant correlations with radial distance were identified; although the observed spectral shapes display an ordering with the longitudinal separation between the spacecraft and the associated solar flare. We also observed a correlation between the spectral index in the intermediate energy range at 70 keV and the strength of the associated solar flare. The correlation disappears at lower and higher energies, suggesting a stronger influence of transport effects at those energies.
Conclusions
We conclude that multiple processes are likely involved in shaping SEE spectra. Our results suggest that the two breaks of the KK triple power law spectra arise from distinct effects, Langmuir-wave generation, and pitch-angle scattering, respectively. Our results also suggest that the break in the double power laws could represent a merger between the first and second breaks of KK triple power laws.